ANALISIS KEBIJAKAN PERLINDUNGAN HUKUM KORBAN MALPRAKTEK PROFESI MEDIS : A LITERATURE REVIEW - Eva Nur Agustin; Shifa Aulia Maghfiroh; Sarah Rania Annisa; Aghnia khoirunnisa; Novita Dwi Istanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem of malpractice cases committed by health workers in Indonesia is still common. The incompetence of health workers is one of the causes of malpractice cases. Malpractice is a medical service that disappoints and harms the patient because the doctor is less successful or fails to seek health and healing for the patient. Medical malpractice perpetrators may be held liable under both civil and criminal law. This study uses a literature review to examine different methods. The purpose of this research is to find out the legal protection policies for victims of malpractice committed by the medical profession. The article search strategy uses an online database, namely Google Scholar and this study uses a systematic review methodology known as PRISMA. The results of this study show that there is legal protection for victims of criminal acts in the medical field under positive criminal law in Indonesia, which is currently carried out by imposing sanctions on perpetrators of criminal acts, namely Law No. 29 of 2004 Article 66 Paragraph 1. In addition to enforcing the malpractice crime law that has been regulated in the Criminal Code to provide stronger guarantees of legal certainty, the handling of medical malpractice and health workers is also regulated in Law No. 36 of 2009 concerning health and Law No. 36 of 2014 concerning health workers.